ANTIFUNGAL ACTIVITY OF SOME PLANT EXTRACTS AGAINST GANODERMA LUCIDUM (CURTIS EX. FR.) KARST., CAUSING BASAL STEM ROT DISEASE IN ARECANUT - RANJANA CHAKRABARTY; G. C. ACHARYA; T. C. SARMA (The Bioscan, 2014)
Basal stem rot disease caused by the fungus, Ganoderma lucidum (Curtis Ex. Fr.) Karst, is the most dreaded disease of arecanut in Assam. The experiment was carried out to test the antifungal activity of aqueous extract of thirty locally available plant species against the test fungus. Pure culture of Ganoderma sp. was isolated from fruiting body of infected arecanut palm. Among the plant species tested, Allium sativum corm extract exerted maximum inhibition with 90.89, 100 and 100 per cent inhibition over control at 5, 10 and 20 per cent conc. respectively, followed by extract of Solanum nigrum with 77.00. 84.11 and 100 per cent inhibition over control at 5, 10 and 20 per cent conc. respectively after 144h of incubation. Leaf extract of Clerodendron infortunatum, Bidens pilosa, Leucas aspera, Spilanthes paniculata, Lawsonia inermis and Cinnamomum verum showed strong inhibitory effect at 20 per cent conc. with 84.00, 83.88, 79.22, 77.22, 76.11 and 72.78 per cent inhibition over control respectively.